Elevations of ventricular lactate levels occur in both chronic fatigue syndrome and fibromyalgia. Issue 1 (2nd January 2017) - Natelson, Benjamin H.; Vu, Diana; Coplan, Jeremy D.; Mao, Xiangling; Blate, Michelle; Kang, Guoxin; Soto, Eli; Kapusuz, Tolga; Shungu, Dikoma C.
ABSTRACT: Background: Chronic fatigue syndrome (CFS) and fibromyalgia (FM) frequently have overlapping symptoms, leading to the suggestion that the same disease processes may underpin the two disorders – the unitary hypothesis. However, studies investigating the two disorders have reported substantial clinical and/or biological differences between them, suggesting distinct pathophysiological underpinnings. Purpose: The purpose of this study was to further add to the body of evidence favoring different disease processes in CFS and FM by comparing ventricular cerebrospinal fluid lactate levels among patients with CFS alone, FM alone, overlapping CFS and FM symptoms, and healthy control subjects. Methods: Ventricular lactate was assessed in vivo with proton magnetic resonance spectroscopic imaging ( 1 H MRSI) with the results normed across the two studies in which the data were collected. Results: Mean CSF lactate levels in CFS, FM and CFS + FM did not differ among the three groups, but were all significantly higher than the mean values for control subjects. Conclusion: While patients with CFS, FM and comorbid CFS and FM can be differentiated from healthy subjects based on measures of CFS lactate, this neuroimaging outcome measure is not a viable biomarker for differentiating CFS from FM or from patients in whom symptoms of the two disorders overlap.